Furyborn eaudiobook - Legrand, Claire (Empirium, 2018)
The stunningly original, must-read fantasy follows two fiercely independent young women, centuries apart, who hold the power to save their world...or doom it. When assassins ambush her best friend, Rielle Dardenne risks everything to save him, exposing herself as one of a pair of prophesied queens: a queen of light, and a queen of blood. To prove she is the Sun Queen, Rielle must endure seven elemental magic trials. If she fails, she will be executed...unless the trials kill her first. One thousand years later, the legend of Queen Rielle is a fairy tale to Eliana Ferracora. A bounty hunter for the Undying Empire, Eliana believes herself untouchable-until her mother vanishes. To find her, Eliana joins a rebel captain and discovers that the evil at the empire's heart is more terrible than she ever imagined. As Rielle and Eliana fight in a cosmic war that spans millennia, their stories intersect, and the shocking connections between them ultimately determine the fate of their world-and of each other. "Epic feminist fantasy." -Melissa Albert, New York Times bestselling author "Truly not to be missed..." -Kendare Blake, #1 New York Times bestselling author